2008
DOI: 10.1152/ajpendo.00640.2007
|View full text |Cite
|
Sign up to set email alerts
|

Ambient glucose levels qualify the potency of insulin myogenic actions by regulating SIRT1 and FoxO3a in C2C12 myocytes

Abstract: Nedachi T, Kadotani A, Ariga M, Katagiri H, Kanzaki M. Ambient glucose levels qualify the potency of insulin myogenic actions by regulating SIRT1 and FoxO3a in C 2C12 myocytes. Am J Physiol Endocrinol Metab 294: E668-E678, 2008. First published January 29, 2008 doi:10.1152/ajpendo.00640.2007.-Nutrition availability is one of the major environmental signals influencing cell fate, such as proliferation, differentiation, and apoptosis, often functioning in concert with other humoral factors, including insulin. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 60 publications
5
31
0
2
Order By: Relevance
“…Similarly, suppression of myogenesis under hypoglycemic conditions appears to be mediated by sortilin. In addition, it has been shown that the glucose-restricted condition inhibits skeletal myoblast differentiation [18], and the overexpression of sortilin in C2C12 cells significantly stimulated myogenic differentiation [7]. These results together with the present findings suggest that sortilin is an important intermediate molecule for glucose-dependent regulation of myogenic differentiation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similarly, suppression of myogenesis under hypoglycemic conditions appears to be mediated by sortilin. In addition, it has been shown that the glucose-restricted condition inhibits skeletal myoblast differentiation [18], and the overexpression of sortilin in C2C12 cells significantly stimulated myogenic differentiation [7]. These results together with the present findings suggest that sortilin is an important intermediate molecule for glucose-dependent regulation of myogenic differentiation.…”
Section: Discussionsupporting
confidence: 82%
“…C2C12 myoblasts were induced to differentiate in low glucose differentiation medium (LG-DM: DMEM containing 5mM glucose + 2% CS) or high glucose differentiation medium (HG-DM: DMEM containing 22.5mM glucose + 2% CS). In our experimental conditions, we had confirmed that the C2C12 myoblasts became hypoglycemic within 24h in LG-DM but not in HG-DM [18]. After inducing differentiation, sortilin expression was examined every 24h.…”
Section: Changes In Glucose Levels Reversibly Control Sortilin Proteimentioning
confidence: 51%
See 1 more Smart Citation
“…Several studies have reported increased SIRT1 protein levels (Balestrieri et al 2008, Kanfi et al 2008, Nedachi et al 2008) and nuclear accumulation (Nedachi et al 2008) under conditions of low glucose concentrations. In line with this, a report showed that glucosamine reduced SIRT1 protein expression in HepG2 cells (Sun et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 was shown to impact on cell survival through physical binding with p53, HSF1, Hif-2a, FOXO, and Ku70 (Dioum et al 2009, Westerheide et al 2009, Gagarina et al 2010 and reviewed in Yamamoto et al (2007). Importantly, SIRT1 and its yeast homolog SIR2 appear to be very sensitive to changes in cellular glucose content such as those occurring upon caloric restriction (Lin et al 2000, Cohen et al 2004, Nisoli et al 2005, Civitarese et al 2007, Chen et al 2008, Kanfi et al 2008, Nedachi et al 2008. In cultured pancreatic b-cells, overexpression of Sirt1 was shown to protect against cytokine toxicity (Lee et al 2009).…”
Section: Introductionmentioning
confidence: 99%